Pola Komunikasi Interpersonal Tokoh Adat Dalam Pewarisan Nilai Budaya Melayu Deli Kepada Remaja Di Desa Hamparan Perak - Adliyana Adliyana; Leylia Khairani (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study aims to describe the interpersonal communication patterns of traditional leaders in transmitting Deli Malay cultural values to youth, and to identify supporting and inhibiting factors. This study employed a qualitative method with a descriptive approach, using interviews, observation, and documentation techniques with traditional leaders and youth as informants. The results indicate that interpersonal communication occurs directly through face-to-face interactions in traditional activities and daily life. Communication is two-way, enabling dialogue, feedback, and closeness between traditional leaders and youth. The cultural values inherited include politeness, respect for elders, togetherness, and religious values. Values are transmitted through advice, role models, and youth involvement in traditional activities. Supporting factors include social closeness, family support, and youth involvement in traditional activities. Meanwhile, inhibiting factors include the influence of modernization, technological developments, differences in mindsets, and low youth interest in local culture. Thus, the effectiveness of adaptive interpersonal communication is the key to maintaining the sustainability of Deli Malay cultural values amidst the development of the times.